Suppression of Ganoderma boninense using benzoic acid: impact on cellular ultrastructure and anatomical changes in oil palm wood - Fernanda, Rozi; Siddiqui, Yasmeen; Ganapathy, Daarshini; Ahmad, Khairulmazmi; Surendran, Arthy (MDPI AG, 2021)
Basal stem rot (BSR) caused by a wood degrading fungus, Ganoderma boninense, is the major constraint in palm oil production. It degrades the wood components and causes palms to collapse, leading to heavy losses. Inefficacy in controlling this disease could be caused by the lack of understanding in how the pathogen establishes itself on the host concerning wood decay stages. This study aimed to understand and determine the role of benzoic acid on the suppression of G. boninense and production of ligninolytic enzymes responsible for wood decay. Further, the alteration in wood component structure due to G. boninense infection and its prevention were studied. Benzoic acid treatment resulted in more than 80% of inhibition in G. boninense growth. SEM and HR-TEM analysis confirmed the antifungal activity of benzoic acid by disruption of mycelial morphology and cellular ultrastructure. Moreover, the membrane permeability assay recorded enhanced cell mortality in benzoic acid treated mycelium. The degradation of oil palm woodblock caused 58.86 % wood dry weight loss at day 120. In contrast, reduction in dry weight loss (58.82%) was recorded in woodblock treated with concentrations of benzoic acid of 5 mM and above. It is concluded that the use of benzoic acid could inhibit or delay pathogen establishment in oil palm wood, leading to the sustainable management of BSR disease. Further, glasshouse and field trials are required to prove the consistency in current findings which may contribute to reduced land expansion to create new disease-free land for oil palm planting.